ANALISIS PERBANDINGAN PENILAIAN KINERJA PERBANKAN MENURUT SE Bl 1997 DAN SE BI 1998 - Lydia Setyawardani (Ekuitas: Jurnal Ekonomi dan Keuangan, 2018)
We can evaluate the bank health from financial  ratios in its financial  statements.  The fi nancial ratios are known as ('AMEL (capital adequacy, asset quality, management, earning, liquidity). The government changes the regulation of evaluation of bank health. The new regulation we use now is SE HI No. 30 23: UPPB, 19 March 1998 and the old one is SE Bl No. 30   2   UPPB. 30 April 1997.